Assessment of first-year students decisions on housing preference in the University of Benin, Nigeria / J.O. Adebiyi, B.L. Tanko and A.K. Oyetunji - Adebiyi, J.O.; Tanko, B.L.; Oyetunji, A.K. (Faculty of Architecture, Planning and Surveying, 2017)
Decent housing plays a very important role in the formative years of any man’s life. Accommodation decisions have become very important in ensuring that man and his immediate family are safe and comfortable. The choice of university accommodation plays a vital role in determining the quality of life the student experiences in the university. Every student needs to put some factors into consideration before making a housing decision. This study aims to explore the factors affecting student’s decision on housing preferences in the university of Benin, Nigeria. A total of 120 structured questionnaires were administered to first year students of the faculty of Environmental Sciences and information obtained forms the benchmark on which the result is based. The data was analyzed using the Relative importance index (RII) and frequency distribution tables. Findings showed that, income of parents or sponsors, price of accommodation, gender of other occupants, proximity to classrooms and other places of interest, security, the age of the student, privacy, availability and frequency of supply of utilities, size of the accommodation and the conduciveness of the environment were the most important factors that students considered in making accommodation decisions in the university of Benin as evidenced by their ranking of preference.